2021
DOI: 10.1155/2021/2012903
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of ADAR Promotes Breast Cancer Progression and Serves as a Potential Therapeutic Target

Abstract: Background. Breast cancer (BC) is the most common cause of cancer death worldwide, and its incidence is increasing every year. This study aims to investigate the expression characteristics of ADAR gene in breast cancer and to explore its role in the occurrence and development of BC and its possible mechanism. Methods. TCGA portal was used to detect the expression of ADAR in cancer including BC, and its correlation with clinicopathological data as well as other genes was analyzed via UALCAN database. The TISCH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…By comparison, analysis of the role of the unique genes in MCF7-ERβ1 cells revealed that the regulation of all but one of the hub genes (PPARG, HIPK2, ZFP36L1, HMGB2 and ALDH1A3) and of 12 more unique genes (ASCL1, ID3, GPNMB, SGK3, BAG3, WDR73, ALKBH1, HIGD1A, FGD3, ACAA2, DOCK8 and AGR3) reportedly favors inhibition of breast cancer cell proliferation and tumorigenicity, induction of cell death and/or better clinical outcome [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. In contrast, in ERβ2-expressing cells, the regulation of the two unique hub genes (CXCL12 and SIX4) and of nine of the other unique genes (INHBE, GADD45B, RPS7, IFIT3, IGFBP3, JAG2, BCL3, GPR37L1 and KRT80) reportedly favors inhibition of cell death, resistance of BC to endocrine therapy and poor clinical prognosis [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Indicative functions reported for all cell-death-related genes uniquely regulated in MCF7-WT, MCF7-ERβ1 and MCF7-ERβ2 cells are presented in Supplementary Tables S10–S12 .…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, analysis of the role of the unique genes in MCF7-ERβ1 cells revealed that the regulation of all but one of the hub genes (PPARG, HIPK2, ZFP36L1, HMGB2 and ALDH1A3) and of 12 more unique genes (ASCL1, ID3, GPNMB, SGK3, BAG3, WDR73, ALKBH1, HIGD1A, FGD3, ACAA2, DOCK8 and AGR3) reportedly favors inhibition of breast cancer cell proliferation and tumorigenicity, induction of cell death and/or better clinical outcome [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. In contrast, in ERβ2-expressing cells, the regulation of the two unique hub genes (CXCL12 and SIX4) and of nine of the other unique genes (INHBE, GADD45B, RPS7, IFIT3, IGFBP3, JAG2, BCL3, GPR37L1 and KRT80) reportedly favors inhibition of cell death, resistance of BC to endocrine therapy and poor clinical prognosis [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Indicative functions reported for all cell-death-related genes uniquely regulated in MCF7-WT, MCF7-ERβ1 and MCF7-ERβ2 cells are presented in Supplementary Tables S10–S12 .…”
Section: Resultsmentioning
confidence: 99%
“…17 OASL may interact with ADAR to promote the proliferation and migration of breast cancer cells. 30 However, the effect of OASL on the progression of STAD has not been reported. In our study, cell experiments verified that OASL knockdown inhibited cell proliferation, migration, and invasion, but promoted apoptosis in STAD cells.…”
Section: Discussionmentioning
confidence: 99%
“…High OASL expression is associated with poor prognosis in patients with PDAC 17 . OASL may interact with ADAR to promote the proliferation and migration of breast cancer cells 30 . However, the effect of OASL on the progression of STAD has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We downloaded the data for protein‐protein interaction (PPI) network construction from the STRING online database. Details were shown in previous research 30 …”
Section: Methodsmentioning
confidence: 99%